Legal Protection of Foreign Direct Investment in the OHADA Area - Ngoya, Dominique (Social Science Research Network, 2021)
This paper analyzes the protection of Foreign Direct Investments in the OHADA area, specifically, its regulation by the Treaty of Organization and Harmonization in Africa of Business Law (OHADA Treaty). It is to restore legal and judicial security within their scope that OHADA member countries have undertaken to harmonize and unify their economic sector legislation to attract foreign investment as a factor in economic development. Several national and international legal instruments are responsible for the protection of foreign direct investment in OHADA countries. Indeed, the volume of foreign direct investment (FDI) to developing countries increased considerably during the 1990s; As Africa is now one of the favorite destinations for Western and even African investors, it is becoming a very profitable continent for investors. However, the issue of regulating or securing foreign investment in African countries is still flawed. The establishment of OHADA, in a way, is in the same direction; if we stick to the purpose of the organization prescribed in paragraph 5 of the preamble to the OHADA Treaty, which states that the purpose of the OHADA law is to "promote the growth of economic activity and encourage investment." Unfortunately, this objective remains only an announcement of the preamble to the Treaty, because of the definition of business law given by Article 2 of that treaty. However, the list of subjects is not exhaustive, investment remains absent. Thus, foreign investment is not regulated by the OHADA Treaty, so even investment-related activities are held by other subjects (corporate law, commercial law, and security law). The omission of FDI in the scope of the OHADA Treaty leads us to raise the question of its regulation.This work proposes a reflection that the OHADA Treaty should be modernized through reform including investment and many other issues to deal effectively with the issue of foreign investment given the ineffectiveness of national and sub-regional instruments in this area.
Keywords: Foreign direct investment; Investment Law; Investment Protection; OHADA